Identity and consciousness in economics - Rizzello, Salvatore (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
This paper introduces the concept of consciousness in the debate on the role of identity in economics. After a brief review of the main issues emerged from this literature, it illustrates two neurobiological theories on the nature of consciousness and provides a contribution towards clarifying two controversial theoretical aspects: how economic agents are aware of the decision making process and the relationship between individual identity and social identity. With the help of some ideas borrowed from quantum physics, which are at the basis of the microbiological processes of human consciousness and generation of knowledge, we refer to the cognitive path from which emerges diversity, the imperfect predictability of human behaviour and the interactive connection between individual and social dimension. Keywords: Identity; consciousness; cognitive economics; personal knowledge; path dependence. Index: 1. Introduction – 2. Identity and economics – 3. Consciousness and identity – 4. Consequences for economic analysis – 5. Concluding remarks – 6. References